2022
DOI: 10.1021/acs.analchem.1c05487
|View full text |Cite
|
Sign up to set email alerts
|

Water Droplet-in-Oil Digestion Method for Single-Cell Proteomics

Abstract: Recent advances in single-cell proteomics highlight the promise of sensitive analyses in limited cell populations. However, technical challenges remain for sample recovery, throughput, and versatility. Here, we first report a water droplet-in-oil digestion (WinO) method based on carboxyl-coated beads and phase transfer surfactants for proteomic analysis using limited sample amounts. This method was developed to minimize the contact area between the sample solution and the container to reduce the loss of protei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…196 Recently, Masuda and colleagues introduced a water droplet-in-oil digestion (WinO) approach. 197 This method uses immiscibility of solvents (water and oil) to reduce sample loss during sample preparation and to increase protein recovery. Briefly, an extraction buffer containing 1 μL of water droplet is prepared with phase transfer surfactants and hydrophobic carboxyl-coated nanomagnetic beads, and then cells are loaded in ethyl acetate to mix with the extraction buffer.…”
Section: Other Recent Developments: Proteochip Wino and Pispamentioning
confidence: 99%
“…196 Recently, Masuda and colleagues introduced a water droplet-in-oil digestion (WinO) approach. 197 This method uses immiscibility of solvents (water and oil) to reduce sample loss during sample preparation and to increase protein recovery. Briefly, an extraction buffer containing 1 μL of water droplet is prepared with phase transfer surfactants and hydrophobic carboxyl-coated nanomagnetic beads, and then cells are loaded in ethyl acetate to mix with the extraction buffer.…”
Section: Other Recent Developments: Proteochip Wino and Pispamentioning
confidence: 99%
“…Inspired by these single-cell MS studies, many innovative methods to prepare samples with minimal volume have been reported, for example, sub-nanoliter volume droplet samples on a hydrophobic polymer film (Fig. 2 C), 23 ) preparing a lysate water droplet-in-oil, 24 ) usage of a commercial picoliter dispenser, 25 ) and microfluidic chip, 26 ) and performing seamless sample preparation and nano-LC separation. 27 )…”
Section: Single-cell Proteomics Via Msmentioning
confidence: 99%
“…Yet, SCP still suffers from several limitations in proteomic depth and throughput. Since the material from individual cells is scarce, several studies focused on reducing losses during sample preparation by process miniaturization (13, 14) and avoiding surface adsorption (15, 16). As one important example, the SCoPE- MS (single-cell proteomics by mass spectrometry) methodology uses sample multiplexing via TMT- labeling to concomitantly increase analyte concentration and throughput (17, 18).…”
Section: Introductionmentioning
confidence: 99%